Non-boltzmann statistics as an alternative to holography - Cantcheff, Marcelo Botta; Nogales, Jose A. C. (World Scientific Publishing, 2006)
An intriguing question related to black hole thermodynamics is that the entropy of a region shall scale as the area rather than the volume. In this essay we propose that the microscopical degrees of freedom contained in a given region of space, are statistically related in such a way that obey a nonstandard statistics, in which case an holographic hypothesis would not be needed. This could provide us with some insight about the nature of degrees of freedom of the geometry and/or the way in which gravitation plays a role in the statistic correlation between the degrees of freedom of a system. © World Scientific Publishing Company.
Keywords: Black hole entropy; Holography; Nonextensive statistics